Characteristics of a Regulator of G-Protein Signaling (RGS) rgsC in Aspergillus fumigatus - Kim, Young; Heo, In-Beom; Yu, Jae-Hyuk; Shin, Kwang-Soo (Frontiers in Microbiology, 2017)
The regulator of G-protein signaling (RGS) proteins have a conserved RGS domain that facilitates the intrinsic GTPase activity of an activated Gα subunit of heterotrimeric G protein, thereby attenuating signal transduction. Among six predicted RGS proteins in the opportunistic human pathogenic fungus Aspergillus fumigatus, only three (FlbA, GprK, and Rax1) have been studied. The unexplored RgsC composed of the Phox-associated (PXA), RGS, Phox homology (PX), and Nexin_C superfamily domains is highly conserved in many ascomycete fungi, suggesting a crucial role of RgsC in fungal biology. To address this, we have investigated functions of the rgsC gene. The deletion () of rgsC causes impaired vegetative growth and asexual development coupled with reduced expression of key developmental regulators. Moreover, rgsC results in accelerated and elevated conidial germination regardless of the presence or absence of an external carbon source. Furthermore, rgsC causes reduced conidial tolerance to oxidative stress. In addition, activities and expression of catalases and superoxide dismutases are severely decreased in the rgsC mutant. The deletion of rgsC results in a slight reduction in conidial tolerance to cell wall damaging agents, yet significantly lowered mRNA levels of cell wall integrity/biogenesis transcription factors, indicating that RgsC may function in proper activation of cell wall stress response. The rgsC mutant exhibits defective gliotoxin (GT) production and decreased virulence in the wax moth larvae, Galleria mellonella. Transcriptomic studies reveal that a majority of transporters is down-regulated by rgsC and growth of the rgsC mutant is reduced on inorganic and simple nitrogen medium, suggesting that RgsC may function in external nitrogen source sensing and/or transport. In summary, RgsC is necessary for proper growth, development, stress response, GT production, and external nutrients sensing.